Stratigraphic revision of Ramírez de Velasco ranges, Santiago del Estero - Leall, P.R. (2011)
In this paper new geologic evidences allow us to complete the stratigraphy of Ramez de Velasco ranges. Granitoids of the igneous basement are included into the Ojo de Agua-Ambargasta complex as the Sumampa Granite which is composed of three facies: facies Para Yacu, Sumampa Viejo and Los Telares. Thin aplitic dykes were included into the same basement as the last magmatic event of the same geological setting. The geochemical signature of these rocks shows meta to peraluminous compositions, which evidence magmatic arc granitoides. Basic dykes, few meters wide and more than one kilometer long, also intrude these granitoids. They are composed of basalts and andesites with calcoalkaline signatures that were correlated with Balbuena formation due to their petrological features. Finally, few and small outcrops of sandstones appears as the only expression of the Neopaleozoic sedimentation. On the basis of all the data obtained we suggest that the Ramíez de Velasco ranges preserve evidences of several geologic processes that took place since the Paleozoic.